Adherence to pharmacological therapy in patients with hansen’s disease - Oliveira, Josiéle Gomes de (2022)
Hansen’s disease, a chronic infectious disease caused by Mycobacterium leprae, is considered a major public health issue. Adherence to pharmacological therapy contributes to the patient’s quality of life and to interrupting the disease transmission chain. Hence, this study analyzes adherence to multidrug therapy in patients with Hansen’s disease treated at a specialized care service in Rondonópolis, Mato Grosso, Brazil. A quantitative, descriptive research was carried out with 63 patients diagnosed with Hansen’s disease and treated at the Specialized Care Service of the municipality of Rondonópolis. Adherence was analyzed using the Morisky-Green test. A total of 31 (49.2%) patients were classified as adherent to treatment. The lowest frequency of adherence was observed in women, aged 51 to 59 years, white, family income ? 2 minimum wages, with up to eight years of schooling, without partners, and with a sewage system in their homes. Statistical difference was observed for the variables gender (p=0.036), detection mode (p=0.008), and clinical form (p=0.028). Results showed low adherence to multidrug therapy. Women, patients with referral detection or collective exams, with undetermined clinical form, tuberculoid or Lepromatous leprosy, are less adherent to polychemotherapy. The findings indicate the need to adopt measures that seek to promote better adherence to pharmacological therapy among patients with Hansen’s disease.